Reclaiming the nation the return of the national question in Africa, Asia and Latin America - Moyo, Sam; Yeros, Paris, 1968- (Pluto Press ; Distributed in the United States of America exclusively by Palgrave Macmillan, 2011)
"This book compares the trajectories of states and societies in Africa, Asia and Latin America under neoliberalism, a time marked by serial economic crises, escalating social conflicts, the re-militarisation of North-South relations and the radicalisation of social and national forces"--P. [4] of cover.